Maternal hyperuricemia and adverse neonatal outcomes in normotensive pregnancies: Evidence from a prospective cohort study in Eastern Uganda - Hassan Abdullahi Hafsa; Marie Pascaline Sabine Ishimwe; Musa Kasujja; Geoffrey Okot; Sawda Abdikarim Sheikh Isse; Hussein Mire Hamdi; Mohamud Mohamed Sadia; Ramlo Abdi Ali; Adam Abdrahim Suliman Ebaid; Maxwell Okello; Ahmed Kiswezi Kazigo; Theodore Nteziyaremye; et al. (PLoS ONE, 2026)
Background Maternal hyperuricemia is a potential biomarker of adverse pregnancy outcomes, but evidence among normotensive women in low- and middle-income countries is limited. We aimed to assess the association between elevated maternal serum uric acid (SUA) levels and adverse neonatal outcomes. Methods We conducted a prospective cohort study at Jinja Regional Referral Hospital, Uganda, from 1 st October 2024–1 st February 2025, enrolling 352 normotensive women in latent labor. SUA was measured using gestational-age–specific cutoffs, classifying women as hyperuricemic or normouricemic. Outcomes included preterm birth, small-for-gestational-age (SGA) birth, stillbirth, and low Apgar score. Poisson regression with robust standard errors estimated adjusted relative risks (aRR) and 95% confidence intervals. Results Adverse neonatal outcomes occurred in 37.5% of participants. Hyperuricemic women had significantly higher composite risk (62.5% vs. 12.5%; aRR = 4.32, 95% CI 2.92–6.39). Hyperuricemia independently predicted preterm birth (aRR = 3.63, 95% CI 1.70–7.72), SGA (aRR = 2.80, 95% CI 1.61–4.86), and stillbirth (aRR = 5.00, 95% CI 1.47–16.99). Maternal age ≥ 40 years, low education, < 4 antenatal visits, previous preterm birth, previous stillbirth, and obesity were also associated with adverse outcomes. Conclusions. Maternal hyperuricemia is a strong predictor of preterm birth, SGA, and stillbirth. Routine SUA screening during antenatal care, combined with closer monitoring of high-risk women, could help improve neonatal outcomes.